Effect of Environmental Conditions in Poultry Houses on the Performance of Laying Hens - Kocaman, Bahar; Esenbuga, Nurinisa; Yildiz, Ahmet; Lacin, Ekrem; Macit, Muhlis (International Journal of Poultry Science, 2005)
This experiment was conducted to determine the effects of environmental factors (ammonia, carbon dioxide, hydrogen sulfide, dust, temperature, relative humidity) on egg production feed consumption and feed conversion ratio. Lohman layers (n = 288, 24 wks of age) were blocked according to the location of cages. In the analysis made, it was observed that air of poultry house and productive performance were significantly affected from seasonal changes. In winter and spring months, the amount of feed consumed per kg egg production was found higher in terms of summer and autumn months. In addition, there was a negative and significant correlation between carbon dioxide and relative humidity and egg production. Also, in case of the existence of the increase in gases of poultry houses, it was determined that feed conversion ratio becomes worse.